Simplified design method of pounding-unseating-prevention device for LRB isolated continuous girder bridge. (January 2023) - Long, Xiaohong; Gui, Shihai; Ma, Yongtao; Turgun, Ahmed; Zhou, Qunlin; Lu, Chunde
Abstract: Although cable restrainer and pull rod restrainer can reduce the seismic response of bridge structures to a certain extent, they cannot have good restrain and anti-pounding functions simultaneously. This paper proposes a simplified design method of a pounding-unseating-prevention device composed of rubber buffer block and steel block. The iterative design method of the device based on the pounding force response spectrum is studied according to the two-dimensional simplified analysis model of the isolated continuous girder bridge. The simplified design method considers the influence of factors, such as the difference in the dynamic characteristics of adjacent structures, ground motion characteristics and site conditions, through the pounding force response spectrum. To evaluate the effectiveness of the design method, nonlinear time history analysis is conducted on the lead rubber bearing (LRB) isolated continuous girder bridge with pounding-unseating-prevention device. The effectiveness of the device and the rationality of the design method are verified by comparing the relative displacement of the pier-girder and the maximum pounding force. Results show that the device designed using this simplified design method can reduce the pounding response of the structure and avoid the pounding of adjacent girders and unseating effectively.